MINERALOGY OF THE VORONTSOVSKOE GOLD DEPOSIT (NORTHERN URALS). PART 3: SULFOSALTS - A.V. Kasatkin; S.Yu. Stepanov; M.V. Tsyganko; R. Škoda; F. Nestola; J. Plášil; E. Makovicky; A.A. Agakhanov; R.S. Palamarchuk (Минералогия)
This paper continues a series of publications devoted to the mineralogy of the Vorontsovskoe gold deposit in the Northern Urals (Kasatkin et al., 2020, 2021). The article reports on sulfosalts of the deposit, their chemical compositions, as well as unit-cell parameters, optical properties and Raman spectra of some minerals. For eight new mineral species discovered by the authors (auerbakhite, vorontsovite, gladkovskyite, gungerite, luboržákite, pokhodyashinite, ferrovorontsovite, tsygankoite), we provide their density, hardness, reflectance spectra and crystal structure. Arsiccioite, benavidesite, bernardite, boscardinite, veenite, weissbergite, vrbaite, heptasartorite, heteromorphite, guettardite, gillulyite, dalnegroite, drechslerite, sicherite, imhofite, christite, cupropolybasite, laffittite, lorándite, manganoquadratite, nowackiite, oyonite, parapierrotite, rebulite, roshchinite, twinnite, philrothite, hutchinsonite, stalderite, écrinsite and enneasartorite are found for the first time in Russian Federation.